Subsidios alimentarios: Dos errores de focalizacion. (Two Errors of Food Aid Targeting. With English summary.) - Cornia, G; Stewart, F (2003)
The central goal of food aid programs is to convey incomes to poor households, In order to minimize the loss of resources it is necessary to correct two errors of targeting in the food care system in developing countries: omission or exclusion of the poor, and inclusion of the not poor.